Improving the speaking learning process to the students of grade VIII through games - Chatarina Heny Eka Purnamu; Joko Priyana (Lingua Pedagogia, 2020)
This study was aimed at improving  the speaking learning process to the students of grade VIII at SMPN 3 Cilacap through games in the academic year of 2013/2014. This classroom action research was carried out in two cycles. The cyclical design consisted of four main steps: (1) planning, (2) action, (3) observation, and (4) reflection. Various games with some supporting activities were implemented in this study. The data were gathered through observations, interview, rating, video/audio recording, and performance tests. The data were analyzed using the interactive qualitative data analysis and descriptive statistics.  The findings show that games which are set up properly involved preliminary activities, game play and closure, together with some supporting activities are able to improve the speaking learning process. The implementation of games is effective to lessen the interference of the native language, lessen the students’ domination in the class, encourage the students’ initiation to speak English, give the students plenty of opportunities to speak as often as possible and encourage the students to focus on fluency rather than accuracy, encourage the students’ confidence, and increase the students’ involvement in the learning process. These improvements lead to the improvements of the students’ speaking skills. The students’ average score in performance test before implementing the actions is 63,39 while after implementing the actions is 81,64. It shows that it increases about 28,77%. It can be inferred that the students’ speaking skills improved after the implementation of the games.